2020
DOI: 10.2298/aoo190531011h
|View full text |Cite
|
Sign up to set email alerts
|

Cross-cultural adaptation and validation of the cancer survivors’ unmet needs measure among gynecological cancer patients in Indonesia

Abstract: Background: The number of gynecological cancer survivors in Indonesia is growing, yet little is recognized about their supportive care needs due to a lack of validated assessment to measure them. This study aimed to culturally adapt the Cancer survivors' unmet needs into Indonesian language and to test its validity and reliability for Indonesian gynecological cancer patients. Methods: We performed the translation and adaptation of the Cancer survivors' unmet needs based on Beaton's cross-cultural adaptation pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(7 citation statements)
references
References 15 publications
(29 reference statements)
0
7
0
Order By: Relevance
“… 14 15 16 17 18 44 45 These adverse effects can pose great challenges for survivors in the process of readaptation after the treatment phase. 46 47 48 49 50 51 Pain during intercourse was a predominant symptom in 10 of the selected studies and causes a great impact on the lives of women, as many avoid sex and abandon their sex life due to fear of the pain they may experience during intercourse. 9 15 18 46 Vaginal dryness was prevalent in several studies, and it has been identified through research that 70% of sexually active women experienced this side effect.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“… 14 15 16 17 18 44 45 These adverse effects can pose great challenges for survivors in the process of readaptation after the treatment phase. 46 47 48 49 50 51 Pain during intercourse was a predominant symptom in 10 of the selected studies and causes a great impact on the lives of women, as many avoid sex and abandon their sex life due to fear of the pain they may experience during intercourse. 9 15 18 46 Vaginal dryness was prevalent in several studies, and it has been identified through research that 70% of sexually active women experienced this side effect.…”
Section: Resultsmentioning
confidence: 99%
“… 9 15 18 46 Vaginal dryness was prevalent in several studies, and it has been identified through research that 70% of sexually active women experienced this side effect. 47 50 51 Currently, with the help of a variety of symptom management offerings, such as vaginal lubricators and targeted therapies, this discomfort can be alleviated for patients. 30 37 49 Studies have reported difficulties for women in adjusting to their altered sex lives and difficulties with intimacy with their partners.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Meanwhile, the main variable in this study, the male partner's unmet supportive care needs, was measured using the Cancer Survivors' Partners Unmet Needs-Indonesia (CaSPUN-I) Questionnaire. [ 17 ] This study adopted 35 items in CaSPUN-I to assess and identify the unmet supportive care needs of participants. Each item was scored as 0 for “no/met need” and 1 for “unmet need.” The items were rated similarly to the CaSPUN-I to measure the unique needs of gynecological cancer survivors for supportive care and services.…”
Section: Methodsmentioning
confidence: 99%
“…[ 18 ] It has demonstrated good internal consistency, validity, and reliability among survivors' partners in Indonesia (Cronbach's alpha 0.97). [ 17 ] Permission for use was granted to the authors. The Indonesian version of the questionnaire was used to collect the data in this research.…”
Section: Methodsmentioning
confidence: 99%